Segmented flow sampling with push–pull theta pipettes. Issue 6 (23rd February 2016) - Saha-Shah, Anumita; Green, Curtis M.; Abraham, David H.; Baker, Lane A.
Abstract : We report development of a mobile and easy-to-fabricate theta pipette microfluidic device for segmented flow sampling. Abstract : We report development of a mobile and easy-to-fabricate theta pipette microfluidic device for segmented flow sampling. The theta pipettes were also used as electrospray emitters for analysis of sub-nanoliter segments, which resulted in delivery of analyte to the vacuum inlet of the mass spectrometer without multiple transfer steps. Theta pipette probes enable sample collection with high spatial resolution due to micron or smaller sized probe inlets and can be used to manipulate aqueous segments in the range of 200 pL to tens of nanoliters. Optimized conditions can enable sampling with high spatial and temporal resolution, suitable for chemical monitoring in biological samples and studies of sample heterogeneity. Intercellular heterogeneity among Allium cepa cells was studied by collecting cytoplasm from multiple cells using a single probe. Extracted cytoplasm was analyzed in a fast and high throughput manner by direct electrospray mass spectrometry of segmented sample from the probe tip.